Pengembangan Video Animasi dengan Pendekatan Problem-Solving untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa SD dalam Pembelajaran IPA - Suliyati, Suliyati; Prastowo, Srihandono Budi; Sutomo, Moh. (Jurnal Paedagogy, 2023)
This research aims to analyze animated learning videos’ validity, practicality, and effectiveness with a problem-solving approach to improving elementary students’ creative thinking skills in science learning. This research method used Research and Development (R&D) using the ADDIE model. The research was conducted in three elementary schools using problem-solving learning syntax. The research instrument used validation sheets, observation sheets, pre-test and post-test questions and was analyzed using the N-Gain test. The learning video validation results obtained 95.8% with a very valid category. The practicality of learning videos in three schools obtained scores between 88.86% and 89.82% in the very practical category. The effectiveness of learning videos based on the N-gain score obtained showed that learning videos based on animation were in the high category. Based on these results, the animated learning videos with the problem-solving approach developed were valid, practical, and effective in improving students’ creative thinking skills in elementary science learning.